Prion Disease - Baldwin, Kelly J.; Correll, Cynthia M. (Seminars in Neurology, 2019)
Prion diseases are a phenotypically diverse set of disorders characterized by protease-resistant abnormally shaped proteins known as prions. There are three main groups of prion diseases, termed sporadic (Creutzfeldt–Jakob disease [CJD], sporadic fatal insomnia, and variably protease-sensitive prionopathy), genetic (genetic CJD, fatal familial insomnia, and Gerstmann–Straussler–Scheinker syndrome), and acquired (kuru, variant CJD, and iatrogenic CJD). This article will review the pathophysiology, genetics, clinical presentations, and diagnostic challenges in patients with prion disease. Case discussions, images, and tables will be used to highlight important characteristics of prion disease and prion mimics.
Keywords: transmissible spongiform encephalopathies; prion disease; Creutzfeldt–Jakob disease; fatal familial insomnia; variant CJD; Gerstmann–Straussler–Scheinker syndrome; kuru; Wernicke–Korsakoff syndrome; Bovine spongiform encephalopathy